The Impact of The Sovereign Credit Rating on The Possibility of Financing External Loans to The Iraqi Economy - Muayad Mahmood *, Zinah; Mohamed Ali Abdul-Latif Al-Ani , Emad (Journal of Economics and Administrative Sciences, 2024)
External loans are a source of credit revenue. The process of obtaining it requires determining the degree of credit risk by predicting the financial solvency of the economy to judge its financial ability to pay the principal and interest dues of the loan at the specified maturity date. Considering that ability is a determinant of the creditworthiness of his economy, the extent to which financing can continue with this external credit source and its cost. The government of Iraq faced the difficulty of financing external loans from the international capital markets with its high return due to the lack of a sovereign credit rating that measures the risk of default through a process to determine the degree of that risk for investors of external lending funds. Therefore, the research came to show the effect of determining the sovereign credit rating on the extent to which the Government of Iraq can finance foreign loans, whether from capital markets or foreign governments and the impact of this classification on the credit facilities granted. The research concluded that the economy of Iraq got a sovereign credit rating within the degree of creditworthiness according to the classification of speculation to reflect the possibility of default in payment due to the dependence of the financial solvency of its economy on oil revenues, as the credit risks rise due to the inability to pay in the event of a decline in prices in the foreign market. However, relative stability within the short term enabled the Iraqi government to obtain foreign loans, with the requirement that Iraq provide guarantees by foreign governments and institutions in exchange for this source of credit.